Comparison and Effect of Persistent Character and Mathematical Process Skills on Fractional Computing Operation Materials in Elementary School - Kamid Kamid; Dwi Agus Kurniawan; Yelli Ramalisa; Rahmat Perdana; Sri Muslimatul Husna; Sabila Eka Septi; Naufal Aqila Kusnadi (Journal of Innovation in Educational and Cultural Research, 2023)
To be able to understand a mathematical problem and be able to express thoughts and arguments, and provide solutions to a problem, students need to have persistent character and mathematical processing skills. This study aims to find out whether there is a comparison of persistent character and mathematical processing skills at SDN 35 Batanghari, SDN 64 Muara Bulian, MIN 3 Batanghari, MIN 2 Batanghari in mathematics and to find out whether there is an influence between persistent character and mathematical processing skills at SDN 35 Batanghari, SDN 64 Muara Bulian, MIN 3 Batanghari, MIN 2 Batanghari in mathematics. The research method used is mixed methods with a sequential explanatory research design. The instrument in this study used character persistence questionnaires and mathematical processing skills. The t-test results obtained from the table show that there is a relationship between the persistence character variable and students' mathematical processing abilities in the subject matter of mathematical fractional computation operations. From the results of the regression test obtained from the table, it can be seen that there is an influence between the sign tenacity variables and the students' mathematical processing abilities in the subject matter of mathematics in fractional computation operations. This research can be used as a reference to pay more attention to student learning persistence because persistence has a significant effect on students' mathematical processing skills at the elementary level. Thus, the researcher hopes that further research can observe the comparison and influence of persistence with mathematical processing skills in other materials.